Psychosocial intervention programme based on the needs of women undergoing termination of pregnancy for foetal anomalies: A modified Delphi study - Ying Wang; Chi Huang; Jiaying Xie; Lihong Zeng; Yaohan Wang; Yanjuan He; Ying Li; Chunxiang Qin (Wiley, 2024)
Abstract Aim To construct a psychosocial intervention programme for women diagnosed with foetal anomalies based on their needs in China. Design A three round‐modified Delphi survey from September to November 2020. Methods In Round 1, based on literature review and qualitative interviews, a face‐to‐face meeting with eight taskforce members was conducted to generate the initial intervention indicators. In Round 2 and 3, 15 experts and three stakeholders (women undergoing termination of pregnancy for foetal anomalies) were invited by email to evaluate the importance of the indicators and built the final psychosocial intervention programme. Results The response rate for both two rounds is 100%. The experts' authority coefficient was 0.86. The Kendall W value of the two rounds ranged between 0.191 and 0.339. A needs‐based psychosocial intervention programme was established, including four periods (denial, confirmation, decision‐making and recovery), three needs‐based supports (information, social and acceptance commitment therapy) and 27 intervention indicators. The mean value of the importance of each index was 4.00-5.00. Further research is required to evaluate whether this programme is realistic and effective for the target audiences.